Diagnostic value of left ventricle strain pattern of hypertensive patients in coronary and cerebrovascular diseases - raheem, qais neamah; Hassan, Tuka Y.; Raheem, Ammar Q.; Al-farhan, Hassan Ali (Journal of the Faculty of Medicine Baghdad, 2021)
Association of Electrocardiographic Left Ventricular Strain Pattern with Coronary Artery Disease and Cerebrovascular Accident in Hypertensive PatientsBackground: Patients diagnosed with hypertension and left ventricular hypertrophy could presented with electrocardiographic changes including criteria of left ventricular hypertrophy, and left ventricular strain pattern( fixed ST depression and T inversion in leads I, avL, V5&6)Objective: To study the impact of electrocardiographic left ventricular strain pattern in hypertensive patient as predictor for coronary artery disease and cerebrovascular accident development.Material and method: a cross sectional hospital based study was conducted during 2012-2017 at Iraqi center for heart diseases including hypertensive patients with normal ECG or LV strain pattern criteria, all patients underwent echocardiography and coronary angiography and the data were collected from patients’ files.Results: The records of 401 hypertensive patients [262(65.3%) males/139(34.7%) females] were included in this study. Their mean age was 60.07 ± 10.8 year. The relation between electrocardiographic left ventricular strain pattern and Coronary Angiography among patients was significant (P